Effects of orange fleshed sweet potato production on the welfare status of rural farmers in Osun State, Nigeria (2019)
Generally, sweet potato is highly adaptable to adverse environmental conditions and also has the potential of increasing food production, income and household food security in many low-income rural communities. Orange fleshed Sweet Potato (OFSP) variety was developed to address health and nutrition problems (Vitamin A deficiency) of Sub-Saharan Africa. OFSP offers new opportunities in terms of shorter period of growth, higher yield, greater tolerance to major stresses, increased carbohydrate and vitamin A content compared to the traditional cultivars. The crop (vines) have been disseminated by research institutes and related agencies for cultivation by farmers. Hence, in this study, the potential of OFSP in improving the welfare status (food, health, education and utility) of the rural farmers in Osun State, Nigeria W3S examined. Purposive sampling technique was used to select three Local Government Areas while 30% of both OFSP and Non-OFSP registered farmers were randomly selected to give 110 respondents. Both questionnaire and FGD were used for data collection while descriptive and inferential statistics were employed for data analyses. Results revealed 56.4% of the respondents were between the age-group of 41-65 years, 85.5% were males, 89.1% were married while 60.9% were educated. Majority (82.7%) have farm sizes between 1-10 acres while only 47.3% have between 4-19 years of farming experience in sweet potato production. Majority (82.5%) of the OFSP farmers have high welfare status compared with low welfare status of all non-OFSP farmers. There was a significant difference (t=9.661) between welfare status of OFSP and Non-OFSP farmers. Education ( 2=52,572), farm size (f0.569) and household size (f0,336) have significant relationships with welfare status of OFSP farmers, In conclusion, cultivation of OFSP has positive effect on the welfare status of the farmers in the in the study area, however, more extension agents should be employed to create awareness about the economic and nutritional values of the crop for sustainable production and increased welfare status of the farmers.